Fatigue crack growth of aluminium alloy 7075-T651 under non-proportional mixed mode I and II loads - Xiaobo Yu; Ling Li; Gwénaëlle Proust (Fracture and Structural Integrity)
This study aims to investigate fatigue growth behaviour in AA7075-T651 under non-proportional mixed mode I and II loads. Fatigue tests were performed under cyclic tension and torsion using a thin-walled tubular specimen with a key-hole style crack starter. After the generation of a single-side mode I pre-crack, varied forms of mixed mode loads were applied, which in most cases led to a short distance coplanar growth followed by a long and stable crack path deviation. It was found that under most of the non-proportional mixed mode load cases, the direction of the deviated crack path could not be reasonably predicted using the commonly accepted maximum tangential stress criterion. Meanwhile, in some cases, the crack path directions could be approximately predicted using the maximum shear stress criterion. It was also confirmed for the first time that a long, stable and noncoplanar shear mode fatigue crack growth could be produced in AA7075T651 under non-proportional mixed mode I and II loads. ©2016 Commonwealth of Australia